An Innovative Process for Efficient Data Evaluation in an Atmospheric Geochemical Survey of Contaminated Soil - Eskvarekova, Erika; Wittenberger, Gabriel; Senova, Andrea; Bakalar, Tomas; Harcarufka, Rastislav (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article focuses on the field of innovative trends for efficient data processing in the conduct of research of organic soil pollution using a soil air analyzer for surveys of soil contamination in situ at industrial enterprises in Slovakia. The content of the article is a discourse of theoretical knowledge from the field of the geological environment; the authors` own survey to monitor the processing and evaluation of the measured values obtained (e.g., CO2, CH4, NEL, BTEX).
Keywords: analyzer; soil contamination; data processing; Windows Power Shell; environment; geochemical survey; analizator; zanieczyszczenie gleby; przetwarzanie danych; środowisko; badania geochemiczne